2017
DOI: 10.1186/s13000-017-0612-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the correlation of vasculogenic mimicry, ALDH1, KiSS-1, and MACC1 in the prediction of metastasis and prognosis in ovarian carcinoma

Abstract: BackgroundRecurrence and metastasis are the usual manifestations of treatment failure of epithelial ovarian carcinoma (EOC). Vasculogenic mimicry (VM; blood supply development often seen in highly aggressive cancers), aldehyde dehydrogenase 1 (ALDH1, cancer stem cell biomarker), KiSS-1 (suppressor of tumor metastasis), and metastasis associated in colon cancer-1 (MACC1) are all useful predictive factors for metastasis and prognosis in various cancers. In this study, we analyzed associations among VM, ALDH1, Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 47 publications
4
42
0
2
Order By: Relevance
“…Moreover, higher plasma MACC1 levels were positively correlated to the tumour status of N 1 or N 2 , M 1 and AJCC III+IV , and also in died CRC patients. These findings were consistent with previous reports in patients with ovarian cancer and pancreatic cancer . Our results further revealed that patients with MACC1 high had an obviously worse survival and a 5‐year survival rate compared with those with MACC1 low , and plasma MACC1 was an significant independent prognostic biomarker for CRC patients, strengthening the issue that MACC1 was a novel and reliable molecule in prognostic prediction as earlier studies emphasized …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, higher plasma MACC1 levels were positively correlated to the tumour status of N 1 or N 2 , M 1 and AJCC III+IV , and also in died CRC patients. These findings were consistent with previous reports in patients with ovarian cancer and pancreatic cancer . Our results further revealed that patients with MACC1 high had an obviously worse survival and a 5‐year survival rate compared with those with MACC1 low , and plasma MACC1 was an significant independent prognostic biomarker for CRC patients, strengthening the issue that MACC1 was a novel and reliable molecule in prognostic prediction as earlier studies emphasized …”
Section: Discussionsupporting
confidence: 93%
“…These findings were consistent with previous reports in patients with ovarian cancer and pancreatic cancer. 13,14 Our results further revealed that patients with MACC1 high had an obviously worse survival and a 5-year survival rate compared with those with MACC1 low , and plasma MACC1 was an significant independent prognostic biomarker for CRC patients, strengthening the issue that MACC1 was a novel and reliable molecule in prognostic prediction as earlier studies emphasized. 1,10 Finally, we evaluate whether MACC1 levels in stratified clinical parameters could improve their prognostic power in CRC patients.…”
Section: In This Context Stein Et Al Firstly Reported That Circulatisupporting
confidence: 68%
“…Oncogenic function of MACC1 and S100A4 has likewise been proposed for ovarian cancer. It was reported that both genes are overexpressed in ovarian cancer and this overexpression was associated with increased migration, chemoresistance, and epithelialto-mesenchymal transition (EMT) (Kikuchi et al, 2006;Li et al, 2015;Yan et al, 2016;Yu et al, 2017;Zhang et al, 2016). However, clinical relevance of MACC1 and S100A4 transcripts as potential bloodbased biomarkers for ovarian cancer patients is completely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Определение кисспептина и его рецептора GPR-54 при проведении иммуногистохимиче-ских (ИГХ) исследований биопсийных образцов опухолей помогает прогнозировать положитель-ный исход заболевания раком яичников у жен-щин [7]. L. Yu et al (2017) при ИГХ-исследовании образцов ткани эпителиального рака яичников установили, что уровень экспрессии KISS1 был значительно ниже, чем при доброкачественных заболеваниях яичников [8]. Однако в другой работе оценивались ИГХ-методом экспрессия и корреляция белка KISS1 в первичных эпите-лиальных опухолях яичников [9].…”
unclassified